Studies on coordination chemistry of a nitrogen–sulfur donor ligand with lighter and heavier metal ions and biological activities of its complexes - H. Tarafder, M. Tofazzal; Asmadi, A.; Talib, Siti M. S.; Ali, A. M.; Crouse, K. A. (Springer, 2001)
Complexes of S-benzyldithiocarbazate (SBDTC) with lighter and heavier metals, viz., CrIII, FeIII, SbIII, ZrIV, ThIV and UVI have been prepared and characterized by elemental analyses, conductivity measurements, and spectral studies. The complexes: [Cr(SBDTCA)3],** [Fe(SBDTCA)3], [Sb(SBDTCA)3], [Sb(SBDTCA)2Cl · H2O], [Zr(O)(SBDTCA)2 · H2O)], [Th(SBDTCA)(NO3)3 · H2O)], and [U(O)2(SBDTCA)2] were all prepared in alkaline media. They were all hexa-coordinated with bidentate, uninegative chelation of the ligand. [Fe(SBDTCA)3], [Sb(SBDTCA)3] and [Sb(SBDTCA)2Cl · H2O] were strongly effective against bacteria giving clear inhibition zones with Pseudomonas aeruginosa and Bacillus cereus. The compounds showed poor antifungal activity. The antimony complexes were strongly cytotoxic against leukemic cells with CD50 values of 3.2-6.7 μg cm-3 as compared to the CD50 value of 14.5 μg cm-3 of the free SbCl3 molecule.